2019
DOI: 10.1007/s00705-019-04215-y
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus and rotavirus infections in children less than five years of age hospitalized with acute gastroenteritis in Indonesia

Abstract: Rotaviruses and noroviruses are the most important viral causes of acute gastroenteritis in children. While previous studies of acute gastroenteritis in Indonesia mainly focused on rotavirus, here, we investigated the burden and epidemiology of norovirus and rotavirus disease. Children less than five years of age hospitalized with acute gastroenteritis were enrolled in this study from January to December 2015 at three participating hospitals. Rotavirus was detected by enzyme immunoassay (EIA), followed by geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 65 publications
(90 reference statements)
5
25
2
Order By: Relevance
“…30 Previous studies reported that NoV as a leading cause of sporadic cases and outbreaks of AGE across all age groups, 5,6 while among children, those with 13 to 24 months were prevalent. 17,34 In this study, NoV infection commonly occurred in children between 13 and 24 months of age, similar to the previous findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…30 Previous studies reported that NoV as a leading cause of sporadic cases and outbreaks of AGE across all age groups, 5,6 while among children, those with 13 to 24 months were prevalent. 17,34 In this study, NoV infection commonly occurred in children between 13 and 24 months of age, similar to the previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…1 Our finding was also compatible with the reports from children and patients with all age groups in other cities (Yogyakarta, Mataram, Jakarta) in Indonesia (18.47%-31.6%). 17,19,20 In some countries that have introduced universal rotavirus vaccination, NoV has become the leading cause of medically attended AGE in children. 30 Previous studies reported that NoV as a leading cause of sporadic cases and outbreaks of AGE across all age groups, 5,6 while among children, those with 13 to 24 months were prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute gastroenteritis (AGE), defined as sudden-onset diarrhea that is unrelated to chronic disease, with or without nausea, vomiting, fever or abdominal pain, is disproportionately common among young children 1 , 2 . Rotavirus (RV) is the most common cause of AGE and the leading cause of AGE-associated mortality in children younger than 5 years of age 2 – 6 . In 2016, more than 258 million episodes of diarrhea and approximately 1.5 million hospitalizations and 128,500 deaths in children younger than 5 years were attributable to RV infection globally 2 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several G/P combinations have been reported, but the most common ones are the six genotypes G1P [8], G2P [4], G3P [8], G4P [8], G9P [8], and G12P [8] which cause up to 75% of human RVA infections worldwide. 3 In Europe RV gastroenteritis (RVGE) was estimated to account for 28% to 52% of AGE cases, and RVA was responsible for up to two-thirds of admissions to hospital and emergency room visits and one-third of primary care consultations for AGE among children. An observational study conducted during the 2004 to 2005 season in seven European countries showed that in Italy the estimated annual incidence rate for AGE was 10.78/100 children, whereas the annual incidence rate for RVGE was 4.70/100 children.…”
Section: Introductionmentioning
confidence: 99%